2021
DOI: 10.1098/rsif.2021.0336
|View full text |Cite
|
Sign up to set email alerts
|

Excessive adventitial stress drives inflammation-mediated fibrosis in hypertensive aortic remodelling in mice

Abstract: Hypertension induces significant aortic remodelling, often adaptive but sometimes not. To identify immuno-mechanical mechanisms responsible for differential remodelling, we studied thoracic aortas from 129S6/SvEvTac and C57BL/6 J mice before and after continuous 14-day angiotensin II infusion, which elevated blood pressure similarly in both strains. Histological and biomechanical assessments of excised vessels were similar at baseline, suggesting a common homeostatic set-point for mean wall stress. Histology f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…Indeed, many animal studies have shown that aortic contraction can be elicited upon stimulation with vasoactive drugs/agents, both ex vivo and in vivo [5,9,10]. Furthermore, we have suggested that such contraction may play a pivotal role in preventing maladaptation and fibrotic remodelling of the aorta in angiotensin II-induced hypertension in mice [9].…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Indeed, many animal studies have shown that aortic contraction can be elicited upon stimulation with vasoactive drugs/agents, both ex vivo and in vivo [5,9,10]. Furthermore, we have suggested that such contraction may play a pivotal role in preventing maladaptation and fibrotic remodelling of the aorta in angiotensin II-induced hypertension in mice [9].…”
mentioning
confidence: 76%
“…Collagen fibres, on the other hand, because of their wavy arrangement in unloaded arteries, get recruited at higher pressures and their gradual uncrimping leads to a nearly exponential pressure-diameter relationship (Fig. 1, hatched area) [9,14,15,17]. Modelling SMC contraction is considerably more complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because we used population-based data for a particular mouse colony, our results hold for the C57BL/6 × 129/SvEv strain, with expected differences for pure C57BL/6 and 129/SvEv mice (cf. Spronck et al, 2021 ). Previous work has characterized regional aortic biomechanics in multiple mouse models, though without associated FSI analyses of the central hemodynamics ( Ferruzzi et al, 2013 ; Bersi et al, 2017 ; Murtada et al, 2020 ; Spronck et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%